An Impingement Cooling Using Swirling Jets Induced by Helical Rod Swirl Generators - Eiamsa-Ard, S.; Nuntadusit, C.; Wongcharee, K.; Chuwattanakul, V. (My University, 2018)
The heat transfer performance of swirling impinging jets (SIJs) was investigated and compared with that of the conventional jet (CIJ). The swirling jets were induced by helical rod inserts (HRs) fitted with pipe nozzles. The helical rod inserts with two different rod diameter to nozzle diameter ratios (d/D) of 0.46 and 0.64 were employed for comparison. Jet-to-plate distance to nozzle diameter ratio (L/D) was varied from 1 to 5 while Reynolds number was fixed at 20,000. The temperature and Nusselt number distributions on the impinged plate were measured and evaluated using thermochromic liquid crystal (TLC) sheet and image processing technique. The experimental results showed that the swirling jet (SJ) at d/D=0.64 gave higher average heat transfer rate than the SJ at d/D=0.46 up to 6.41% and the conventional jet (CJ) up to 35.05%. In addition, Nusselt number peak of swirling jets increased as jet-to-plate distance decreased.
Keywords: Heat transfer; helical rod; impinging jet; swirling jet; thermochromic liquid crystal